PEMBERDAYAAN IBU-IBU PKK DALAM UPAYA DETEKSI DINI PENYAKIT DEGENERATIF DI KELURAHAN BALUWARTI, SURAKARTA - puspitasary, kiki; Ningrum, Andriani Noerlita; Novitasari, Meliana; Yulianto, Dwi Joko; Indarto, Indarto (LPPM Institut Pendidikan Nusantara Global, 2023)
Degenerative disease is a condition that occurs due to a decrease in the function of a tissue or organ due to the aging process. It is not uncommon for elderly people to realize this disease only when the disease is already in a serious condition with complications, resulting in an increase in morbidity and mortality rates, as well as a decrease in the elderly's quality of life and a decrease in the elderly's ability to carry out daily activities. One of the early detections carried out is routine checks for three body conditions that can cause various degenerative diseases, namely, checking blood sugar levels, checking uric acid levels, checking cholesterol, and checking blood pressure. Early detection can be done by empowering cadres of PKK women in the environment around where the elderly live. The Baluwarti sub-district area is one of the areas in Surakarta that has elderly people with degenerative diseases. Because of this history, there is a need for control efforts from the government and private sector. One of the efforts is to empower PKK women cadres to carry out early detection of degenerative diseases. The method used in this activity is an educational approach and health examination. The results of the health examination obtained in this activity were elderly people with high blood sugar levels, namely 48.1%; uric acid levels above normal, namely 61.5%; cholesterol levels above normal, namely 53.8%; and high blood pressure, namely 55.8%. This shows that the majority of elderly people in the Baluwarti Village area suffer from degenerative diseases.